Effects and central mechanism of electroacupuncture and MRI-navigated rTMS for PSD: study protocol for an fMRI-based single-center, randomized, controlled, open-label trial - Lu, Hai; Wang, Yang; Shen, Diwen; Ruan, Jianguo; Lu, Jiaming; Wang, Linlin; Song, Yang; Fan, Jia; Li, Dongna; Shi, Lijing; Xia, Meng; Xu, Tianshu (Frontiers in Psychiatry, 2024)
Background Post-stroke depression (PSD) is the most common mental complication after stroke and has a serious impact on functional outcomes and quality of life for stroke patients. Antidepressants are the first-line treatment for PSD; however, many reported side effects remain. Clinical research and practice guidelines have shown that electro-acupuncture (EA) or rTMS have a positive effect on PSD. However, there are few clinical studies on EA and MRI-navigated rTMS for PSD that explore the fMRI-based central mechanism in depression. Methods In this randomized, controlled, open-label trial, 64 patients with PSD will be randomly allocated into the experiment group (n = 32) or control group (n = 32). The experiment group will receive EA and MRI-navigated rTMS and the control group will receive MRI-navigated rTMS treatment, in 12–20 sessions over 4 weeks. In addition, 10 healthy people for fMRI scanning will be recruited as a healthy control group without any intervention. The primary outcome will be the change from baseline in the Hamilton Depression Scale-24 item (HAMD-24) scores at week 4. The primary analysis of the central mechanism will mainly involve cortical morphology, local spontaneous brain activity, and the default mode network (DMN) functional connectivity based on fMRI at 0 and 4 weeks. Secondary outcomes will include the neuro-patho-physiological and quality of life changes in cortical excitability, determined using the motor evoked potential test (MEP), National Institutes of Health Stroke Scale (NIHSS), EuroQol Five Dimensions Questionnaire (EQ-5D) Scale, Modified Barthel Index (MBI) Scale, and Health Scale of Traditional Chinese Medicine (HSTCM). Additional indicators will include the Acceptability Questionnaire and Health Economics Evaluation (cost-effectiveness analysis) to assess the acceptability and economic practicality of the treatment under study. Outcomes will be assessed at baseline and post intervention. Discussion EA and MRI-navigated rTMS therapy could become an alternative treatment for PSD, and it is expected that this trial will provide reliable clinical evidence and a potential central mechanism for the future use of EA and MRI-navigated rTMS for PSD. Clinical trial registration NCT05516680, ClinicalTrials.gov (registered in August 2022).